2022
DOI: 10.3389/fenvs.2022.876540
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Mapping of Gas Stored in Sediments of Shallow Aquatic Systems Linked to Methane Production and Ebullition Patterns

Abstract: Bubble-mediated transport is the predominant pathway of methane emissions from inland waters, which are a globally significant sources of the potent greenhouse gas to the atmosphere. High uncertainties exist in emission estimates due to high spatial and temporal variability. Acoustic methods have been applied for the spatial mapping of ebullition rates by quantification of rising gas bubbles in the water column. However, the high temporal variability of ebullition fluxes can influence estimates of mean emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 75 publications
1
8
1
Order By: Relevance
“…The range of PMP rates in the sediment of the reservoir (up to 12.8 mgCH 4 L −1 d −1 ) was lower than the range reported for other impoundments in the same region (up to 25.0 mgCH 4 L −1 d −1 in Wilkinson et al, 2015) and higher than the values reported for a subtropical reservoir in Brazil (up to 6.0 mgCH 4 L −1 d −1 in Marcon, Sotiri, et al, 2022). The highest PMP rates were measured in the top sediment layers, which had higher organic matter content (LOI).…”
Section: Spatial Distribution Of Methane In the Sedimentcontrasting
confidence: 67%
See 2 more Smart Citations
“…The range of PMP rates in the sediment of the reservoir (up to 12.8 mgCH 4 L −1 d −1 ) was lower than the range reported for other impoundments in the same region (up to 25.0 mgCH 4 L −1 d −1 in Wilkinson et al, 2015) and higher than the values reported for a subtropical reservoir in Brazil (up to 6.0 mgCH 4 L −1 d −1 in Marcon, Sotiri, et al, 2022). The highest PMP rates were measured in the top sediment layers, which had higher organic matter content (LOI).…”
Section: Spatial Distribution Of Methane In the Sedimentcontrasting
confidence: 67%
“…The areal gas content in the sediment was estimated from the EA400 echo‐sounder data following Marcon, Sotiri, et al. (2022). The 200 kHz measurements were processed using the Sonar5‐Pro software (Lindem Data Acquisition, Oslo, Norway), in which the magnitude of the maximum acoustic backscatter near the sediment surface is exported together with its geographic coordinates for each ping (sound pulse).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oil and gas are critically needed for the state (for example, to maintain the stable operation of public infrastructure and public institutions), households and businesses. The sustainability of the oil and gas markets is to fully meet the demand, but this is becoming increasingly difficult every year, as the "clean" energy industry is actively developing, and the demand for oil and gas seems to be increasingly unpredictable (Popkova and Sergi, 2021;Marcon et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The average concentration of CH 4 in the fresh bubbles was 35% (4%-65%). As inMaeck et al (2014) andMarcon et al (2022), we used this percentage to convert the volumetric ebullition fluxes to CH 4 ebullitive fluxes again using the ideal gas law. We used the CH 4 concentration of the fresh bubbles as we observed that a considerable CH 4 loss from the bubble traps occurred during deployment (75% decrease in concentration in 23 days).…”
mentioning
confidence: 99%